2014
DOI: 10.1007/s40484-014-0031-9
|View full text |Cite
|
Sign up to set email alerts
|

Exon expression QTL (eeQTL) analysis highlights distant genomic variations associated with splicing regulation

Abstract: Alternative splicing is a ubiquitous mechanism of post-transcriptional regulation of gene expression and produces multiple isoforms from the same genes. Expression quantitative trait loci (eQTL) has been a major method for finding associations between gene expression and genomic variations. Differences in alternative splicing isoforms are resulted from differences in the expression of exons. We propose to use exon expression QTL (eeQTL) to study the genomic variations that are associated with splicing regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In a large scale human blood cell expression QTLs study [ 12 ], eeQTLs also showed the strongest enrichments of GWAS variants, followed by sQTLs and geQTLs. Thus, focusing on exon-level QTLs, including eeQTLs and sQTLs, could increase the chance of finding regulatory variants for complex traits, as proposed by Guan et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a large scale human blood cell expression QTLs study [ 12 ], eeQTLs also showed the strongest enrichments of GWAS variants, followed by sQTLs and geQTLs. Thus, focusing on exon-level QTLs, including eeQTLs and sQTLs, could increase the chance of finding regulatory variants for complex traits, as proposed by Guan et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since most of the known disease-causing mutations occur in exons, genetic methods that focus on protein-coding regions in the genome are effcient in identifying potentially pathogenic mutations (Xue et al, 2019). Therefore, the examination of exons may help us to understand the genetic architecture of SCZ beyond the gene-level (Guan et al, 2014; Ramasamy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…arrays specifically designed to accurately quantify exons vs RNA sequencing). The accurate quantification of exons is essential to understand the genetic architecture of schizophrenia beyond the gene-level 38,39 .…”
Section: Introductionmentioning
confidence: 99%
“…In dairy cattle, Xiang et al [ 12 ] showed that eeQTL overlapped with geQTL and sQTL. Consequently, the combined analysis of geQTL, eeQTL and sQTL may increase the chance to identify loci that regulate gene expression [ 12 , 17 ]. However, to our knowledge, eQTL have not been analyzed in sheep, although it is one of the major farm species for human consumption.…”
Section: Introductionmentioning
confidence: 99%